Вредност серумских Тх1/Тх2 цитокина у комбинацији са туморским маркерима у дијагнози ХР-ХПВ-позитивног рака грлића материце: Serum Th1/Th2 cytokines and tumor markers in cervical cancer - Cao, Xia; Zhang, Xuemei; Zhang, Jingpo; Zhong, Xiaodang; Hu, Shanshan (Journal of Medical Biochemistry, 2025)
Objective: To analyze the value of serum helper T-cell 1 (Th1)/helper T-cell 2 (Th2) cytokines combined with tumor markers in the diagnosis of high-risk human papillomavirus (HR-HPV)-positive cervical cancer. Methods: Forty-nine patients with HR-HPV-positive cervical cancer admitted to the hospital from January 2020 to June 2024 were selected as the study group, and 49 patients with HR-HPV-positive benign cervical diseases of the same age group admitted to the hospital during the same period were selected as the control group. The basic data, serum Th1/Th2 cytokines [interleukin (IL)-10, IL-6, interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α)], and tumor markers [squamous cell carcinoma antigen (SCCAg), carbohydrate antigen 199 (CA199) levels and cytokeratin 19 fragment antigen 21-1 (CYFRA21-1)] of the two groups were compared, and the serum Th1/Th2 cytokine levels of patients with different clinicopathological characteristics in the study group were compared. Pearson correlation analysis was used to analyze the correlation between the levels of serum Th1/Th2 cytokines and tumor markers in patients with HR-HPV-positive cervical cancer. A receiver operating characteristic (ROC) curve was drawn to analyze the value of serum Th1/Th2 cytokines and tumor markers in the diagnosis of HR-HPV-positive cervical cancer. Results: The levels of serum IL-10, IL-6, IFN-Y, TNF-a, SCC-Ag, CA199 and CYFRA21-1 in the study group were greater than those in the control group (P<0.05). The levels of serum IL-10, IL-6, IFN-γ and TNF-α in patients at stages III–IV of the International Federation of Obstetrics and Gynecology (FIGO) in the study group were all greater than those in patients at stages ⅰ–II (P<0.05), and the levels of serum IL-10, IL-6, IFN-γ and TNF-A in patients with a myometrial invasion depth ≥1/2 were all greater than those in patients with a myometrial invasion depth <1/2 (P<0.05). The levels of serum IL-10, IL-6, IFN-Y and TNF-an in patients with HR-HPV-positive cervical cancer were positively correlated with the levels of SCC-Ag, CA199 and CYFRA21-1 (P<0.05). The AUCs of IL-10, IL-6, IFN-Y and TNF-a for the single diagnosis of HR-HPV-positive cervical cancer were 0.809, 0.773, 0.801 and 0.794, respectively, and the AUCs of SCC-Ag, CA199 and CYFRA21-1 for the single diagnosis of HR-HPV-positive cervical cancer were 0.831 and 0, respectively. 728, 0.789. The AUC of the combined diagnosis of HR-HPV-positive cervical cancer by serum IL-10, IL-6, IFN-Y, TNF-a, SCC-Ag, CA199, and CYFRA21-1 was 0.927. The AUC of the combined diagnosis was greater than that of the individual diagnosis of each index (Z=2.116, 2.690, 2).341, 2.565, 1.957, 3.351, 2.631, P=0.034, 0.007, 0.019, 0.010, 0.039, 0.001, 0.009). Conclusion: The combined detection of serum Th1/Th2 cytokine imbalance (elevated IL-6 and IL-10) and tumor markers (SCC, CA125) can significantly improve the diagnostic accuracy of HR-HPV-positive cervical cancer and provide a high-value serological auxiliary basis for the early identification of cervical cancer progression.